Metabolomic profiling combined with network analysis of serum pharmacochemistry to reveal the therapeutic mechanism of Ardisiae Japonicae Herba against acute lung injury - Han, Xiao-Xiao; Tian, Yan-Ge; Liu, Wen-Jing; Zhao, Di; Liu, Xue-Fang; Hu, Yan-Ping; Feng, Su-Xiang; Li, Jian-Sheng (Frontiers in Pharmacology, 2023)
Introduction: Acute lung injury (ALI) is a common and devastating respiratory disease associated with uncontrolled inflammatory response and transepithelial neutrophil migration. In recent years, a growing number of studies have found that Ardisiae Japonicae Herba (AJH) has a favorable anti-inflammatory effect. However, its serum material basis and molecular mechanism are still unknown in ALI treatment. In this study, metabolomics and network analysis of serum pharmacochemistry were used to explore the therapeutic effect and molecular mechanism of AJH against lipopolysaccharide (LPS)-induced ALI. Methods: A total of 12 rats for serum pharmacochemistry analysis were randomly divided into the LPS group and LPS + AJH-treated group (treated with AJH extract 20 g/kg/d), which were administered LPS (2 mg/kg) by intratracheal instillation and then continuously administered for 7 days. Moreover, 36 rats for metabolomic research were divided into control, LPS, LPS + AJH-treated (5, 10, and 20 g/kg/d), and LPS + dexamethasone (Dex) (2.3 × 10−4 g/kg/d) groups. After 1 h of the seventh administration, the LPS, LPS + AJH-treated, and LPS + Dex groups were administered LPS by intratracheal instillation to induce ALI. The serum pharmacochemistry profiling was performed by UPLC-Orbitrap Fusion MS to identify serum components, which further explore the molecular mechanism of AJH against ALI by network analysis. Meanwhile, metabolomics was used to select the potential biomarkers and related metabolic pathways and to analyze the therapeutic mechanism of AJH against ALI. Results: The results showed that 71 serum components and 18 related metabolites were identified in ALI rat serum. We found that 81 overlapping targets were frequently involved in AGE-RAGE, PI3K-AKT, and JAK-STAT signaling pathways in network analysis. The LPS + AJH-treated groups exerted protective effects against ALI by reducing the infiltration of inflammatory cells and achieved anti-inflammatory efficacy by significantly regulating the interleukin (IL)-6 and IL-10 levels. Metabolomics analysis shows that the therapeutic effect of AJH on ALI involves 43 potential biomarkers and 14 metabolic pathways, especially phenylalanine, tyrosine, and tryptophan biosynthesis and linoleic acid metabolism pathways, to be influenced, which implied the potential mechanism of AJH in ALI treatment. Discussion: Our study initially elucidated the material basis and effective mechanism of AJH against ALI, which provided a solid basis for AJH application.